CCL7 and olfactory transduction pathway activation play an important role in the formation of CaOx and CaP kidney stones - Zhang, Qiankun; Wei, Hhuiling; Huang, Gang; Jin, Lie (Frontiers in Genetics, 2024)
Background: The deposition of calcium oxalate (CaOx) and calcium phosphate (CaP) is the most common cause of kidney stone disease (KSD). Whether KSDs caused by CaOx and CaP have common genetic targets or signaling pathways remained unclear. Methods: The present study utilized public data GSE73680 to analyze differentially expressed genes (DEGs) between CaOx or CaP tissues and normal tissues, respectively. Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of co-DEGs were performed. The protein-protein interaction (PPI) network was constructed to identify hub genes, and the top hub gene was selected for gene set enrichment analysis (GSEA). Finally, real-time PCR of patients’ urine was performed to validate the bioinformatic results. Results: In total, 155 significantly co-upregulated DEGs and 64 co-downregulated DEGs were obtained from the datasets. The GO analysis showed that DEGs were significantly enriched in chemical stimulus in sensory perception, detection of chemical stimulus in sensory perception of smell, and olfactory receptor activity. The KEGG analysis showed that the olfactory transduction pathway was significantly enriched. According to PPI, 10 genes were identified as the hub genes, and CCL7 was the top hub gene. The olfactory transduction, maturity-onset diabetes of the young, linoleic acid metabolism, and fat digestion and absorption were significantly enriched in the high-CCL7 subgroup by GSEA. In total, 9 patients who had primarily CaOx mixed with some CaP stones and 9 healthy subjects were enrolled. The RT-PCR results showed that CCL7 level in the stone group was significantly higher than that in the control group (P<0.05). For the olfactory transduction pathway, the expression of OR10A5, OR9A2, and OR1L3 was significantly up-regulated in the stone group compared with the control group (P<0.05). Conclusions: CCL7 may play a key role in the development of both CaOx and CaP, and this process may depend on olfactory transduction pathway activation.